(untitled) (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2020)
This paper explores the absence and presence of women in the sea of the Aeneid. In the first section we observe that no Trojan woman is mentioned in the navigations towards Italy. They are almost completely absent until Book V, where they try to burn the ships because they are exhausted from seafaring. The remaining Trojans are then selected according to their seafaring and warfare skills; therefore, we suggest that the sea plays a key role in defining the epic hero in the Aeneid. Moreover, this absence of women in the representation of seafaring seems to be an epic motif inspired by Homer and Apollonius Rhodius. In the second section we study the presence of Dido and Cleopatra at sea. Dido is interesting because of her ability to sail for several purposes: exile, love and war. This might be inspired by elegiac patterns, since the only examples of women willing to sail in the poem are women in love. These characters link feminity, love, sea and war in a way that is exceptional in epic and may be due to elegiac influences.